O caráter compulsório da utilização da rede de abastecimento de água e esgotamento sanitário como mecanismo de gestão dos recursos hídricos na cidade de Manaus/Am - Silva, José Clibas Macedo Souza da (2019)
The importance of the group of laws required in the sanitation sector controlling process - The sanitation sector controlling by laws is a crucial condition to the country development, particularly due to its role as a mechanism associated to protect the public health and the enviromental concerns. It can be watched from the sewage treatment or from the preservation of hidric resources perspective. Despite of the Federal Law nº 11.445/07, there is a lack of support from the regulatory instituitions, especially associated to promoting public development policies, according to the World Health Organization (WHO) study, which concluded that for each US$ 1 invested in water and sewage treatment, US$ 4, 3 (four dollars and 30 cents) in health costs in the world. Equally salutary is the creation of mechanisms to conciliate, in an articulated way, the national water resources policy (Federal Law nº 9.433/97), with basic sanitation throughout the national territory, considering the regional, economic and geographical aspects, especially regarding the irregular distribution of water resources in the country. For this reason, basic sanitation can not be treated as just a public service, separated from water resources management and regulation instruments, but rather an approach that is in line with the systematic proposal in Federal Laws nº 9.433/97 and 11.445/07 that the lack of basic sanitation infrastructure coupled with the disorderly exploitation of water resources leads to pollution of water and groundwater. The city of Manaus, in spite of had been pioneer in water supply and sewage treatment in Brazil, has historically been facing innumerable problems related to these subjects, arising from the negligence of the competent authorities who has being shown unprepared to bring discipline to the service suppliers. The present study analyzed the state and municipal legislation applicable to the topic, suggested editing a specific bill for the problem of compulsory connection to services, proposed the adoption of agreements signed with the Public Authorities, already used in other States and that brought practical results at a low cost, and lastly, it suggested the implementation of public policies aimed at the universalization of basic sanitation and correct management of water resources, currently used in a disorderly manner, in absolute disagreement with Federal Law nº 9443/97.